Nutritional composition, techno-functional properties and sensory analysis of pan bread fortified with kenaf seeds dietary fibre - Mat Ramlan, Nurul Ainaa Farhanah; Mohammad, Salma Malihah; Karim, Roselina; Syed Muhammad, Sharifah Kharidah; Ismail, Maznah; Zawawi, Norhasnida (Penerbit Universiti Kebangsaan Malaysia, 2021)
Kenaf seeds are underutilized source of food with good source of dietary fiber, protein, essential oil, and phytocompounds. The objectives of this study were to determine the nutritional composition of kenaf seeds, the techno-functional properties of kenaf seeds dietary fibre (KSDF), and sensory analysis of pan bread fortified with dietary fibre that was extracted from kenaf seeds. Analyses showed that kenaf seeds are rich in dietary fibre (28.87 g/ 100 g), protein (27.07 g/ 100 g), oil (23.78 g/100 g) and mineral (5.55 g/100 g). The dietary fibre that was extracted through enzymatic hydrolysis (KSDF (EH)) exhibited significantly (p < 0.05) greater water-binding capacity (WBC), oil-binding capacity (OBC) and viscosity than non-enzymatic hydrolyzed kenaf seeds dietary fibre (KSDF (NEH)) and defatted kenaf seed meal (DKSM). Different formulations of bread were prepared by replacing 10% of wheat flour with wheat bran fibre (positive control), rice bran fibre and KSDF, with white bread unfortified with fibre as negative control. Addition of 10% KSDF to bread formulation significantly (p < 0.05) reduced bread height, volume, specific volume, water activity and firmness, and increased proofing time and bread surface colour. Results from the sensory evaluation of the bread samples also showed that KSDF bread was the most acceptable in comparison to rice bran and wheat bran fortified breads. This study shows that kenaf seed has valuable source of dietary fibre with the potential to be used as a functional ingredient in the development of functional breads.